Hubungan Antara Asupan Serat Dengan KejadianKonstipasi Pada Pekerja Di PT. Tiga Serangkai Surakarta - Wulandari, Mayriza, Siti Zulaekah, A., M.si, Elida Soviana, S.Gz., M.gizi (2016)
Background: Constipation is defecation in the form of less frequent bowel movement, unsatisfied sensation to defecate, painful to defecate, and hard stools consistency. One of the potential dangers to cause health problems in the workplace is the danger associated with unhealthy lifestyles. Such unhealthy life style is eating foods with low fiber but high fat. Low fiber intake can lead to the occurrence of constipation. Objective: The purpose of this study was to determine the fiber intake on constipation occurrence of PT. Tiga Serangkai Surakarta workers. Methods: This study applied observational design with cross sectional approach. There were 46 workers taken as the samples of this study. The data was obtained by using simple random sampling method. The data of fiber intake was obtained by using semi-quantitative FFQ method and the data of constipation occurrence was obtained by using questionnaire. The statistical test applied was Chi Square test. Results: The result of the study indicated that 34.8% of the respondents have good fiber intake and 65.2% of the respondents have less fiber intake. Workers who do not experience constipation are 65.2% and workers who experience constipation are 34.8%. Based on the results of the Chi Square correlation analysis, obtained the value of p = 0.026, there is a relationship of fiber intake on the occurrence of constipation. Conclusion: There is a relationship of fiber intake on the occurrence of constipation of PT. Tiga Serangkai Surakarta workers.